2006
DOI: 10.1002/ijc.21645
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of human prostate cancer growth, osteolysis and angiogenesis in a bone metastasis model by a novel mechanism‐based selective gelatinase inhibitor

Abstract: Metastasis to the bone is a major clinical complication in patients with prostate cancer (PC). However, therapeutic options for treatment of PC bone metastasis are limited. Gelatinases are members of the matrix metalloproteinase (MMP) family and have been shown to play a key role in PC metastasis. Herein, we investigated the effect of SB-3CT, a covalent mechanism-based MMP inhibitor with high selectivity for gelatinases, in an experimental model of PC bone metastases. Intraperitoneal (i.p.) treatment with SB-3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
92
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 91 publications
(94 citation statements)
references
References 35 publications
2
92
0
Order By: Relevance
“…To block MMP-9, we used the specific inhibitor, SB-3CT. SB-3CT is a highly selective mechanism-based gelatinase inhibitor with particular specificity for MMP-9 and has previously been shown to specifically inhibit MMP-9-driven pathways in disease models in vivo (Gu et al, 2005;Bonfil et al, 2006). We verified this selectivity in vitro; SB-3CT inhibited MMP-9-but not MMP-2-mediated gelatinase activity in medium from IL-1␤-treated glial cells.…”
Section: Methodssupporting
confidence: 52%
“…To block MMP-9, we used the specific inhibitor, SB-3CT. SB-3CT is a highly selective mechanism-based gelatinase inhibitor with particular specificity for MMP-9 and has previously been shown to specifically inhibit MMP-9-driven pathways in disease models in vivo (Gu et al, 2005;Bonfil et al, 2006). We verified this selectivity in vitro; SB-3CT inhibited MMP-9-but not MMP-2-mediated gelatinase activity in medium from IL-1␤-treated glial cells.…”
Section: Methodssupporting
confidence: 52%
“…The efficacy of SB3-CT was demonstrated in several distinct models where the functional activity of gelatinases was relevant to the disease. Thus, intraperitoneal treatment with SB-3CT (50 mg/kg) inhibited intraosseous growth of human PC3 cells within the marrow of human fetal femur fragments previously implanted in SCID mice (21). In a transient focal cerebral ischemia model of stroke in mice, MMP-9 contributes directly to neuron apoptosis and brain damage (22) by degrading the extracellular matrix laminin.…”
Section: Invasion-promoting Mt1-mmp In Cancermentioning
confidence: 96%
“…These MMPIs contain a specific group that coordinate the Zn 2+ in the active site, resulting in a conformational change and a covalent attachment that prevent MMP dissociation. 25 The first mechanism-based inhibitor of MMPs was SB3CT, a selective inhibitor toward MMP-2 and MMP-9, that, in preclinical studies, has shown anticancer properties, 26 as well …”
Section: Exogenous Synthetic Mmp Inhibitorsmentioning
confidence: 99%